Three new species of Indochinamon Yeo & Ng, 2007 (Crustacea: Brachyura: Potamoidea: Potamidae) from Vietnam, with a redescription of Ranguna (Ranguna) kimboiensis Dang, 1975 - Naruse, Tohru; Quynh, Nguyen Xuan; Yeo, Darren C. J. (Zootaxa, 2011)
Three new species of Indochinamon Yeo & Ng, 2007, are described from Vietnam. The poorly known Vietnamese species Indochinamon kimboiense (Dang, 1975) is redescribed. The holotype of I. kimboiense is lost, and a topotypic specimen is designated as the neotype. Indochinamon bavi n. sp. from Ba Vi National Park, Ha Tay Province, and I. phongnha n. sp. from Phong Nha, Quang Binh Province, are allied to I. kimboiense, but can be distinguished by the characters of the carapace, chela and male first pleopod. Indochinamon dangi n. sp. is allied to I. lipkei (Ng & Naiyanetr, 1993) [type locality northern Thailand], but can be distinguished by characters of the carapace, telson, and male first pleopod.